History Smashers: Pearl Harbor - Messner, Kate; Meconis, Dylan (New York : Random House, 2020)
"A highly-designed and illustrated (including graphic novel panels) overview of the truths and lies about the attack on Pearl Harbor"--Provided by the publisher.
War overseas -- Warning signs -- Countdown to disaster -- This is not a drill! -- The USS Arizona -- After the attack -- This is war! -- Treatment of Japanese Americans -- America at war -- Time to remember, time to heal.
Includes chronology.
Includes bibliographical references (pages 180-187) and index.
Junior Library Guild
Ages 10-13.
Grades 5-8.
1000
Keywords: Pearl Harbor (Hawaii), Attack on, 1941 -- Juvenile literature; World War, 1939-1945 -- Juvenile literature. -- Causes; Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Causes; Pearl Harbor (Oahu, Hawaii), Attack on, 1941; World War, 1939-1945 -- Causes; Japan -- Juvenile literature. -- Foreign relations -- United States; United States -- Juvenile literature. -- Foreign relations -- Japan; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Japan; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Japan